ISOTOPE RENOGRAM IN ECTOPIC KIDNEY - Taher, M. A. (The ASEAN Journal of Radiology, 2023)
Ultrasonography (USG), may provide some clue to diagnose an ectopic kidney, however, functional confirmation is best done by isotope renogram, as depicted by the rare cases reported below.